2003
DOI: 10.1074/jbc.m306378200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative α-Ketoglutarate Dehydrogenase Inhibition via Subtle Elevations in Monoamine Oxidase B Levels Results in Loss of Spare Respiratory Capacity

Abstract: Age-related increases in brain monoamine oxidase B (MAO-B) and its ability to produce reactive oxygen species as a by-product of catalysis could contribute to neurodegeneration associated with Parkinson's disease. This may be via increased oxidative stress and/or mitochondrial dysfunction either on its own or through its interaction with endogenous or exogenous neurotoxic species. We have created genetically engineered dopaminergic PC12 cell lines with subtly increased levels of MAO-B mimicking those observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 63 publications
4
72
0
2
Order By: Relevance
“…Moreover, studies of the response of intact isolated nerve terminals to oxidative stress demonstrated that, although the aconitase enzyme was the most vulnerable to oxidative damage, it is the inhibition of the 2-oxoglutarate dehydrogenase complex that limits the amount of NADH available for the respiratory chain (Tretter and Adam-Vizi, 2000). Similar conclusions were also drawn following treatment of brain cells with monoamine oxidase (Kumar et al, 2003). These results suggest that in these systems the 2-oxoglutarate dehydrogenase complex exhibits a large proportion of the control resident in the TCA cycle.…”
supporting
confidence: 73%
“…Moreover, studies of the response of intact isolated nerve terminals to oxidative stress demonstrated that, although the aconitase enzyme was the most vulnerable to oxidative damage, it is the inhibition of the 2-oxoglutarate dehydrogenase complex that limits the amount of NADH available for the respiratory chain (Tretter and Adam-Vizi, 2000). Similar conclusions were also drawn following treatment of brain cells with monoamine oxidase (Kumar et al, 2003). These results suggest that in these systems the 2-oxoglutarate dehydrogenase complex exhibits a large proportion of the control resident in the TCA cycle.…”
supporting
confidence: 73%
“…Genetic studies considered polymorphisms in the DLST (encoding E2k) or DLD (encoding E3) genes to be a risk factor for the manifestation of Parkinson or Alzheimer diseases (43,44). Increased oxidative stress is one plausible link between KGDHc deficiency and neurodegeneration, because KGDHc contains a labile Fe-S center, and is sensitive to a number of oxidants including 4-hydroxy-2-nonenal, H 2 O 2 , NO, peroxynitrite, hypochlorous acid, and mono-N-chloramine (34,(45)(46)(47).…”
Section: Reduction Of Flux Through Tca Cycle Via Inhibition Of Kgdhc Bymentioning
confidence: 99%
“…These oxidation processes are important in maintaining physiological levels of dopamine and free dietary amines in our body and proper functioning of the central nervous system. Age related increases in the expression levels of MAOB in neural tissues [2,3] are implicated in several neurological disorders like, Parkinson's and Alzheimer's diseases and selective MAOB inhibitors are clinically proven drug adjuvants for treating these disorders [4,5].…”
Section: Introductionmentioning
confidence: 99%